Enhancing Educational Methods for Electric Machines and Drives through Open-Source Robotics - Ugarte, Nicolas Rebollo; Van Cleemput, Marco; Spolmink, Ruben; Lemeire, Jan (E-Learning in Industrial Electronics, ICELIE, IEEE International Conference on, 2024)
This paper introduces an innovative educational robot designed to enhance learning in electric machines, drives, and power electronics through its user-friendly and easily implementable features. The robot, developed as a modular and open-source platform, facilitates hands-on learning across multiple disciplines, including mathematics, physics, programming, and artificial intelligence. By providing all design files, source code, and schematics on a publicly accessible platform, the project supports customization and expansion, allowing users to adapt and build upon the base robot for diverse educational applications. This approach not only improves understanding of both hardware and software principles but also aligns with modern educational methodologies that leverage advanced tools to enrich the learning experience. The link to the GitLab project can be found here: https://gitlab.com/etrovub/learningrobots/projects/educationalmodular-robot